Perilaku Lentur Panel Beton Semi-Precast pada Daerah Lapangan Tanpa Metode Perkuatan Elemen Pracetak: Tinjauan pada 1, 2 dan 3 Panel - Umi Khoiroh; Suprapto Siswosukarto; Bambang Supriyadi (Semesta Teknika, 2009)
A slab where only the lower portion of the floor slab is prefabricated and receives the top layer of floor slab which is cast in situ, in the context of this research is called semi-precast. For small projects, the transportation, storage, and installation of precast units can be a problem. There will be more problem if it is located in congested urban area. For this reason, precast slab panel system in smaller size and weight was introduced. The precast concrete element which is has a rough surface was predicted capable to act as composite, although no shear reinforcement method was used. The objective of this research is to study the characteristic behavior of semi-precast panel without shear reinforcement method on its interface. The characteristic investigated includes flexural capacity, stiffness, ductility, and failure mode of the slab. In this study, the specimens were divided into two groups. The first group is monolith slab that consists of one, two, and three panel(s). Each panel has 120 mm thickness, 3000 mm span length, and 200 mm width of concrete slab. The second group is semi-precast slab that consists of one, two, and three panel(s). Each panel has 70 mm thick precast slab that serves as formwork for 50 mm in situ concrete layer, to form a 120 mm thick of concrete slab. Dimension and shape between semi-precast and monolith slabs are identical. All specimens were tested under static load and failure load. Experimental results revealed that the stiffness of semi-precast slabs is lower than the monolith slab. More number of panels reduced stiffness differences between semi-precast and monolith slab. It also increases the value of stiffness and flexural capacity of the slabs. The failure mode and crack pattern is classified as flexure. Existence of interface plane which is using no shear reinforcement method can decrease the value of stiffness and flexural capacity of the slab. From the results, it is shown that the slip occurred on the semi-precast slab’s interface. It is predicted that the slip was due to the influence of no shear reinforcement on the interface.